Puberdade e maturidade sexual de tourinhos senepol, criados semi-extensivamente na região do Triângulo Mineiro - MG - Gilson Passos de Moraes (2012)
The Senepol breed is a Bos taurus taurus adapted to tropical climate. In Brazil, has been used in crossbreeding with Zebu, seeking to increase the productive and reproductive efficiency in beef cattle. But few studies have been reported on the reproductive aspects of the race, especially about puberty and sexual maturity. The objective of this research was to determine the development andrological, serum testosterone and total protein in the seminal plasma in young bulls of the Senepol breed, according to age at puberty and sexual maturity (1º Step), and defines the Classification Andrological by points (CAP) and the libido of the animals to 16.22 months old (2º Step). In the first step were used 13 bulls, pure source, with mean age of 12,22 ± 0,16 months, managed on pasture and supplemented with commercial feed (1 kg / animal / day), Soledad from the farm, located in Uberlândia-MG. Every 30 ± 2 days, for a period of 120 days, it was evaluated: body weight (BW), scrotal circumference (SC), physical and morphological semen, profile of serum testosterone (T) and concentration of protein in seminal plasma (PTPS). Andrological data were determined according to the criteria of the Brazilian College of Animal Reproduction. The profile of serum testosterone was determined by solid-phase radioimmunoassay. The total concentration protein in seminal plasma was analyzed by the method of Bradford (1976). In the second step, 13 Senepol bulls with 16,22± 0,16 months of age were divided into two groups, mature (MS) and sexually immature (IM), and submitted to the CAP and the libido test. The determination of CAP was conducted according to scrotal circumference and sperm condition. Libido test was carried out in the cattle shed, individually for each Bull, in the presence of six heifers, with five in estrus. In 1º step, the experimental design was randomized block, now in 2º Step was used a completely randomized design. Statistical analysis was performed using SAS statistical package (SAS, 2002). In 1º step, for ages to puberty (13,22 ±0,16 months) and sexual maturity (16,25 ±0,16 months), it was evaluated, respectively, BW (kg) 304,07 ±12,98 and 374,00 ±18,53; SC (cm) 28,15 ±0,55 and 32,50 ±0,06; sperm motility (%) 23,84 ±5,06 and 66,66 ±5, 16; total sperm in the ejaculate (x106) 88,84 ±7,23 and 801,93 ±136,52; major sperm defects (%) 69,84 ± 6,85 and 13,16 ± 0,98; defects total sperm (%) 82,30 ± 9,00 and 23,16 ± 4,26; T (ng / mL) 8,85 ±1,95 and 6,51 ± 1,38 and PTPS (mg / mL) 18,60 ± 5,89 and 16,88 ± 3,12. In Phase 2, the group of animais with sexual maturity presented higher (p<0,05) BW (374,00 ±18,53 Kg); SC (32,05 ±0,06 cm); average daily gain (0,745 grams) and testicular growth (5.16 cm) than the group of immature animals. Only 46,20% of 13 animals evaluated in CAP were satisfactory score above 60 points. High libido was reported in 57,15% of animals with full sexual maturity and 42,85% of the sexually immature. The profile of serum testosterone was higher in the bulls group with high libido that the average libido. Senepol breed bulls showed the evolution of andrological parameters associated with the development of weight gain and profile association between serum testosterona and sexual behavior.